?-Fe2O3 nanoparticles filled polyvinyl alcohol as potential biomaterial for tissue engineering scaffold - Ngadiman, N.; Idris, A.; Irfan, M.; Kurniawan, Denni; Yusof, N.; Nasiri, R. (Elsevier, 2015)
© 2015 Elsevier Ltd. Maghemite (?-Fe < inf > 2 < /inf > O < inf > 3 < /inf > ) nanoparticle with its unique magnetic properties is recently known to enhance the cell growth rate. In this study, ?-Fe < inf > 2 < /inf > O < inf > 3 < /inf > is mixed into polyvinyl alcohol (PVA) matrix and then electrospun to form nanofibers. Design of experiments was used to determine the optimum parameter settings for the electrospinning process so as to produce elctrospun mats with the preferred characteristics such as good morphology, Young's modulus and porosity. The input factors of the electrospinnning process were nanoparticles content (1-5%), voltage (25-35kV), and flow rate (1-3ml/h) while the responses considered were Young's modulus and porosity. Empirical models for both responses as a function of the input factors were developed and the optimum input factors setting were determined, and found to be at 5% nanoparticle content, 35kV voltage, and 1ml/h volume flow rate. The characteristics and performance of the optimum PVA/?-Fe < inf > 2 < /inf > O < inf > 3 < /inf > nanofiber mats were compared with those of neat PVA nanofiber mats in terms of morphology, thermal properties, and hydrophilicity. The PVA/?-Fe < inf > 2 < /inf > O < inf > 3 < /inf > nanofiber mats exhibited higher fiber diameter and surface roughness yet similar thermal properties and hydrophilicity compared to neat PVA PVA/?-Fe < inf > 2 < /inf > O < inf > 3 < /inf > nanofiber mats. Biocompatibility test by exposing the nanofiber mats with human blood cells was performed. In terms of clotting time, the PVA/?-Fe < inf > 2 < /inf > O < inf > 3 < /inf > nanofibers exhibited similar behavior with neat PVA. The PVA/?-Fe < inf > 2 < /inf > O < inf > 3 < /inf > nanofibers also showed higher cells proliferation rate when MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assay was done using human skin fibroblast cells. Thus, the PVA/?-Fe < inf > 2 < /inf > O < inf > 3 < /inf > electrospun nanofibers can be a promising biomaterial for tissue engineering scaffolds.